PENGARUH PENGETAHUAN INVESTASI, PENDAPATAN DAN KEMAJUAN TEKNOLOGI TERHADAP MINAT INVESTASI MASYARAKAT USIA PRODUKTIF DI REKSA DANA SYARIAH MELALUI APLIKASI BIBIT - Al Farizi, Muhammad Hafidz; Ajeng Kartika Galuh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Investment is one of the crucial matters in people’s personal financial management. Therefore, younger generations have started to make investments in capital markets. Indonesia has the largest potential of becoming the largest capital market globally. Unfortunately, Islamic capital market in the country, especially Islamic mutual funds, is still far behind the conventional ones. Therefore, in order to ensure that the huge potential is not wasted, effective measures to increase people’s intention for investment in Islamic capital market, especially in Islamic mutual funds, are required. The objective of this research is to investigate the effects of investment knowledge, income, and technological advancement on the intention of productive-age people to invest in Islamic capital market, particularly Islamic mutual funds, through Bibit. Using random sampling, 100 people were selected as the respondents. The results of the data analysis using multiple linear regression indicate that investment knowledge, income, and technological advancement influence the intention of productive-age people to invest in Islamic mutual funds through Bibit.